METODE TAHFIDZUL ALQURAN DI RUMAH TAHFIZH MIFTAHUL JANNAH KOTA MEDAN - Fatimah Rahma; Darliana Sormin; Candra Wijaya (Ristekdik : Jurnal Bimbingan dan Konseling, 2019)
The method applied in the Tahfzih Miftahul Jannah House in the process of memorizing the Koran is: the method of tasmi ', wahdah, takrir and sima'i. the method of 'mummy' is divided into two, namely the 'morning deposit' and the repetition of the 'mule' in the afternoon. Metodetasmi 'is an activity of depositing the memorization of the Koran of the santri to one of the ustaz or ustzah respectively. The method of wahdah, takrir, and sima'I is a method that is applied by santri individually to seek memorization before depositing it to the cleric or cleric.Keywords: Method, Tahfiz Alquran, Miftahul Jannah